2006
DOI: 10.1111/j.1524-4725.2005.31610
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Ointment versus Petrolatum for Management of Auricular Wounds

Abstract: There is no statistically significant difference between the use of gentamicin ointment and petrolatum in the prevention of postoperative auricular suppurative chondritis. The data also demonstrate a disproportionate number of cases of inflammatory chondritis in the gentamicin-treated group. This study supports the cost-effective and potentially less irritating use of petrolatum for wound care in this difficult to manage area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…[22][23][24] Other clinical trials comparing the efficacy of wound-healing treatments randomize patients to receive one of two or J AM ACAD DERMATOL VOLUME 64, NUMBER 3 more treatments. 13,14,25 Although these trials provide valid outcomes in overall efficacy and safety, they are not designed for subject ranking of wound appearance. The study design in this trial allowed healing to be assessed in wounds that represent a substantial proportion of the types of wounds that dermatologists create every day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] Other clinical trials comparing the efficacy of wound-healing treatments randomize patients to receive one of two or J AM ACAD DERMATOL VOLUME 64, NUMBER 3 more treatments. 13,14,25 Although these trials provide valid outcomes in overall efficacy and safety, they are not designed for subject ranking of wound appearance. The study design in this trial allowed healing to be assessed in wounds that represent a substantial proportion of the types of wounds that dermatologists create every day.…”
Section: Discussionmentioning
confidence: 99%
“…29,33,34 In addition, head-to-head trials have demonstrated that there is no difference in infection rates between wounds treated with topical antibiotics versus antibiotic-free ointments, whereas irritation and allergic contact dermatitis are increased with topical antibiotics. 13,14,25 This study was not powered to demonstrate any preventive effect of topical antibiotics to reduce the rate of infection, or to demonstrate noninferiority. However, although limited by its size, this study confirms the findings of these earlier studies and demonstrates that both products are equally fast and efficacious in promoting wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen confession phase begins immediately and lasts for months. In this phase, collagen synthesis begins by fibroblasts and done stimulation of macrophages [8][9][10][11][12]. Inflammation maintenance and scarce vessel formation comprise the most noticeable causes of delayed wound healing [13].…”
Section: Introductionmentioning
confidence: 99%
“…11 In contrast, there is considerable evidence that topical antibiotics can cause ACD. 3,9,10,12 In addition, several topical antibiotics have been shown to have cytotoxic effects on human fibroblasts and keratinocytes at clinically relevant doses. 13 Polysporin (Poly/Bac) (polymyxin B sulfate/bacitracin zinc) (Johnson & Johnson, New Brunswick, NJ), bacitracin, and polymyxin B have all been shown to significantly decrease cell proliferation of fibroblasts and reduce the number of viable keratinocytes during in vitro studies when administered at clinical doses.…”
mentioning
confidence: 99%